2016
DOI: 10.1016/j.euroecorev.2016.02.019
|View full text |Cite
|
Sign up to set email alerts
|

The effects of group composition in a strategic environment: Evidence from a field experiment

Abstract: Recent theoretical and empirical studies have explored the effect of group membership and identity on individual decision-making. This line of research highlights that economic models focusing on the individual as the sole entity in the decision-making environment potentially miss critical features. This study takes this literature in a new direction by overlaying a field experiment onto a setting where groups have arisen naturally. Our experimental laboratory is large open air markets, where we are able to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…In particular participants are less likely to tell the truth if other "committee members" hold different social identities. List et al (2016) show that social identity affects the propensity of sellers to collude (by setting the same or similar prices) in a field experiment conducted in a large open air market. In both studies, deviations from standard game theoretical predictions are related to social identity.…”
Section: This Special Issuementioning
confidence: 97%
See 1 more Smart Citation
“…In particular participants are less likely to tell the truth if other "committee members" hold different social identities. List et al (2016) show that social identity affects the propensity of sellers to collude (by setting the same or similar prices) in a field experiment conducted in a large open air market. In both studies, deviations from standard game theoretical predictions are related to social identity.…”
Section: This Special Issuementioning
confidence: 97%
“…In sum, the research articles in this special issue contain overwhelming evidence of discrimination based on ethnic, religious, racial, gender or minimal social identities. Social identity affects behaviour in a range of important situations including market transactions for consumption goods (List et al, 2016;Zussman, 2016), labour markets (Mobius et al, 2016; tions (Krawczyk and Smyk, 2016) or leadership decisions (Finseraas et al, 2016;Gangadharan et al, 2016). The research also has identified several potentially important mechanisms that seem to contribute to discrimination or discriminatory attitudes.…”
Section: Articles By Hombres and Nunziatamentioning
confidence: 99%
“…We find that participants in treatments with experimentally induced group 29 identification have more favorable prior beliefs about the performance of their randomly assigned 30 group members in an intelligence test than have participants in a control condition. Moreover, 31 we find that group identification affects how participants process information when updating their 32 1 Akerlof & Kranton (2000) have integrated this insight into an economic model of identity, and there is a growing number of empirical studies that demonstrate the general relevance of social identities for various economic domains such as, e.g., social preferences (Ben-Ner et al, 2009;Chen & Li, 2009), coordination problems (Chen & Chen, 2011), cooperation in social dilemmas (Goette et al, 2006;Chen et al, 2014), risk and time preferences (Benjamin et al, 2010), or decision making in strategic environments (e.g., Le Coq et al, 2015;List et al, 2016;Rong et al, 2016). See also Lane (2016) for a meta-analysis of experimental work on social identity in economics.…”
mentioning
confidence: 99%
“…They provide evidence that competitive interactions reduce pro-sociality in general, irrespective of whether the interaction partner is an in-or outgroup member. List, Neilson, and Price (2016) provide evidence from a field experiment that pricing decisions and deviations from the rational selfish prediction are related to group membership.…”
Section: Introductionmentioning
confidence: 94%